Answer and work down below
To solve such questions we need to know more about expression.
<h2 /><h2>Expression
</h2>
In mathematics, an expression is defined as a set of numbers, variables, and mathematical operations that are formed according to rules which are dependent on the context.
<h2 /><h2 /><h2>Given to us,</h2>
![2\sqrt[4]{16x}-2\sqrt[4]{2y}+3\sqrt[4]{81x}-4\sqrt[4]{32y}+5\sqrt[4]{x}-4\sqrt[4]{32y}+5\sqrt[4]{x}-16\sqrt[4]{2y}+13\sqrt[4]{4}-10\sqrt[4]{2y}+35\sqrt[4]{x}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=2%5Csqrt%5B4%5D%7B16x%7D-2%5Csqrt%5B4%5D%7B2y%7D%2B3%5Csqrt%5B4%5D%7B81x%7D-4%5Csqrt%5B4%5D%7B32y%7D%2B5%5Csqrt%5B4%5D%7Bx%7D-4%5Csqrt%5B4%5D%7B32y%7D%2B5%5Csqrt%5B4%5D%7Bx%7D-16%5Csqrt%5B4%5D%7B2y%7D%2B13%5Csqrt%5B4%5D%7B4%7D-10%5Csqrt%5B4%5D%7B2y%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-18%5Csqrt%5B4%5D%7B2y%7D)
rearranging we get,
![=2\sqrt[4]{16x}+3\sqrt[4]{81x}+5\sqrt[4]{x}+5\sqrt[4]{x}+13\sqrt[4]{4}+35\sqrt[4]{x}-2\sqrt[4]{2y}-4\sqrt[4]{32y}-4\sqrt[4]{32y}-16\sqrt[4]{2y}-10\sqrt[4]{2y}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D2%5Csqrt%5B4%5D%7B16x%7D%2B3%5Csqrt%5B4%5D%7B81x%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B13%5Csqrt%5B4%5D%7B4%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-2%5Csqrt%5B4%5D%7B2y%7D-4%5Csqrt%5B4%5D%7B32y%7D-4%5Csqrt%5B4%5D%7B32y%7D-16%5Csqrt%5B4%5D%7B2y%7D-10%5Csqrt%5B4%5D%7B2y%7D-18%5Csqrt%5B4%5D%7B2y%7D)
we know that,
![\sqrt[4]{81}=3\\\sqrt[4]{16}=2\\\sqrt[4]{32}=2\sqrt[4]{2}\\](https://tex.z-dn.net/?f=%5Csqrt%5B4%5D%7B81%7D%3D3%5C%5C%5Csqrt%5B4%5D%7B16%7D%3D2%5C%5C%5Csqrt%5B4%5D%7B32%7D%3D2%5Csqrt%5B4%5D%7B2%7D%5C%5C)
therefore,
![=4\sqrt[4]{x}+9\sqrt[4]{x}+5\sqrt[4]{x}+5\sqrt[4]{x}+13\sqrt[4]{x}+35\sqrt[4]{x}-2\sqrt[4]{2y}-8\sqrt[4]{2y}-8\sqrt[4]{2y}-16\sqrt[4]{2y}-10\sqrt[4]{2y}-18\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D4%5Csqrt%5B4%5D%7Bx%7D%2B9%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B5%5Csqrt%5B4%5D%7Bx%7D%2B13%5Csqrt%5B4%5D%7Bx%7D%2B35%5Csqrt%5B4%5D%7Bx%7D-2%5Csqrt%5B4%5D%7B2y%7D-8%5Csqrt%5B4%5D%7B2y%7D-8%5Csqrt%5B4%5D%7B2y%7D-16%5Csqrt%5B4%5D%7B2y%7D-10%5Csqrt%5B4%5D%7B2y%7D-18%5Csqrt%5B4%5D%7B2y%7D)
taking
and
as common
=![[(\sqrt[4]{x})(4+9+5+5+13+35)]-[(2+8+8+16+10+18)(\sqrt[4]{2y})]](https://tex.z-dn.net/?f=%5B%28%5Csqrt%5B4%5D%7Bx%7D%29%284%2B9%2B5%2B5%2B13%2B35%29%5D-%5B%282%2B8%2B8%2B16%2B10%2B18%29%28%5Csqrt%5B4%5D%7B2y%7D%29%5D)
Further simplifying
![=71\sqrt[4]{x}-62\sqrt[4]{2y}](https://tex.z-dn.net/?f=%3D71%5Csqrt%5B4%5D%7Bx%7D-62%5Csqrt%5B4%5D%7B2y%7D)
Learn more about the expression:
brainly.com/question/13947055?referrer=searchResults
Answer:
x = 3
x = (-1)/2
x = 13/4
Step-by-step explanation:
Solve for x:
(2 x)/3 + 15 = 17
Put each term in (2 x)/3 + 15 over the common denominator 3: (2 x)/3 + 15 = (2 x)/3 + 45/3:
(2 x)/3 + 45/3 = 17
(2 x)/3 + 45/3 = (2 x + 45)/3:
1/3 (2 x + 45) = 17
Multiply both sides of (2 x + 45)/3 = 17 by 3:
(3 (2 x + 45))/3 = 3×17
(3 (2 x + 45))/3 = 3/3×(2 x + 45) = 2 x + 45:
2 x + 45 = 3×17
3×17 = 51:
2 x + 45 = 51
Subtract 45 from both sides:
2 x + (45 - 45) = 51 - 45
45 - 45 = 0:
2 x = 51 - 45
51 - 45 = 6:
2 x = 6
Divide both sides of 2 x = 6 by 2:
(2 x)/2 = 6/2
2/2 = 1:
x = 6/2
The gcd of 6 and 2 is 2, so 6/2 = (2×3)/(2×1) = 2/2×3 = 3:
Answer: x = 3
______________________________________________________
Solve for x:
3 x - x + 8 = 7
Grouping like terms, 3 x - x + 8 = (3 x - x) + 8:
(3 x - x) + 8 = 7
3 x - x = 2 x:
2 x + 8 = 7
Subtract 8 from both sides:
2 x + (8 - 8) = 7 - 8
8 - 8 = 0:
2 x = 7 - 8
7 - 8 = -1:
2 x = -1
Divide both sides of 2 x = -1 by 2:
(2 x)/2 = (-1)/2
2/2 = 1:
Answer: x = (-1)/2
_______________________________________
Solve for x:
4 (2 x - 6) = 2
Divide both sides of 4 (2 x - 6) = 2 by 4:
(4 (2 x - 6))/4 = 2/4
4/4 = 1:
2 x - 6 = 2/4
The gcd of 2 and 4 is 2, so 2/4 = (2×1)/(2×2) = 2/2×1/2 = 1/2:
2 x - 6 = 1/2
Add 6 to both sides:
2 x + (6 - 6) = 1/2 + 6
6 - 6 = 0:
2 x = 1/2 + 6
Put 1/2 + 6 over the common denominator 2. 1/2 + 6 = 1/2 + (2×6)/2:
2 x = 1/2 + (2×6)/2
2×6 = 12:
2 x = 1/2 + 12/2
1/2 + 12/2 = (1 + 12)/2:
2 x = (1 + 12)/2
1 + 12 = 13:
2 x = 13/2
Divide both sides by 2:
x = (13/2)/2
2×2 = 4:
Answer: x = 13/4
Answer:
Seven crore eighty thousands sixty-seven.
Step-by-step explanation:
70080067
Seven crore eighty thousands sixty-seven.
Answer:
I SUCK AT WORD PROBLEMS TOOOO LOL
Step-by-step explanation: